(untitled) (Experimental biology, 2015)
In this article, in gerontological age groups calculation the HR has been made in relation to R–R to an interval on a basis electrocardiogram analyses. Thus, the studies have shown that at elderly, senile and longlivers of various type cardiac arrhythmias are found out. The results of our studies shown that in the population of North-Western region of Azerbaijan belonging to gerontological age groups, dysfunctions of the cardiovascular system interfere affect the normal process of ageing. in addition toecological factors also play an important role in the development of such changes. All these processes substantiallyaffect the longevity index and active longevity in the population of the NorthWest area of Azerbaijan.